Nugget Daging Ayam Afkir Tersutitusi Otak Sapi (Dafita) Komposisi Kimia Dan Organoleptik - Tasse, Andi M; Nurhinaya, I; Hafid, Harapin (PROSIDING SEMINAR NASIONAL AGRIBISNIS, 2015)
The study was conducted to evaluate to palatability chicken’s nugget a result of subsitution of layer chiken meat with cow’s brain via chemical compotion and organoleptic test. The experimen was conducted at Animal Husbandry Departemen Laboratory, Faculty Animal Science, Halu Oleo University, Kendari in July 20012 until September 2012. Research using Completely Randomized Design, 4 treatments and 3 replications. The treatment is subsitute the rejected layer chicken with the cow brain, consisting of N1 = meat of rejected layer chicken 100% and cow brain 0%, N2 = meat of rejected layer chicken 85 % and cow brain 15%, N3= meat of rejected layer chicken 75 % and cow brain 25%, and N4 = meat of rejected layer chicken 65 % and cow brain 35 %. Variabel of this research include of test chemical (moisture, protein, fat, carbohydrates, and ash) and organoleptic test (color, aroma, textur, flavor, tenderness and general performance). The result obtained that substitution of the meat of rejected layer chiken with cow brain is 10% to 30 % increase moisture and carbohydrate of nuggets. Substitution of the meat of rejected layer chiken with cow brain is 15 % to 25 % decrease protein in the nugget, the substitution of meat layer chiken with cow brain protein levels of 15 % to 35 % lower levels of fat and ash in the nugget. Color, aroma, texture, flavor, tenderness and general performance of the substitution of chicken nuggets layer rejected by cow brain 10 % to 30 % obtaining the everage score of 3 to 4 is considered quite liked and preferred by consumers. In conclusion, substitution of salvage meat of layer chicken with cow brain nugget influence on the chemical nature and does not affect the organoleptic quality of the product.